The Evaluation of Dental Anxiety in Primary School Children: A Cross-Sectional Study from Romania - Ramona Vlad; Anca Maria Pop; Peter Olah; Monica Monea (MDPI AG, 2020)
Current data report that high levels of dental anxiety in children have a negative impact on oral health. The aim of this study was to measure dental anxiety, based on the Abeer Children Dental Anxiety Scale (ACDAS) used as a self-reported measure and to correlate its values with the salivary cortisol levels. The study was conducted in 2019 and included 389 children aged 6-9 years old; evaluation of dental anxiety and saliva sampling were performed. The influence of gender on the presence of dental anxiety was analyzed using Fisher's exact test, the salivary cortisol level was compared between anxious and non-anxious children and was further correlated with the ACDAS score (p < 0.05). Girls had higher odds of experiencing dental anxiety (odds ratio: 1.533, p = 0.041). Salivary cortisol levels were higher in anxious compared to non-anxious children (median 1.251 vs. 1.091 ng/mL, p < 0.001) and showed a positive moderate correlation with the ACDAS score (r = 0.411, p < 0.001). Children aged 6-9 years have a high prevalence of dental anxiety, with girls being more susceptible to this condition. Salivary cortisol levels are higher in anxious children and correlate positively with the ACDAS score, proving that ACDAS can be used for the detection of dental anxiety.